Feasibility of future transition to 100% renewable energy: Recent progress, policies, challenges, and perspectives - Al-Shetwi A.Q.; Abidin I.Z.; Mahafzah K.A.; Hannan M.A. (Elsevier Ltd, 2025)
The global transition to 100% renewable energy (RE) aims to mitigate climate change, enhance energy security, and achieve sustainable energy systems. Despite numerous studies, reports, plans, and pathways toward achieving this target, comprehensive research on its feasibility is lacking. Thus, this paper aims to provide an in-depth analysis of the current status, feasibility, and future perspectives of transitioning to 100% RE. It addresses two main questions: ?Is a global transition to 100% RE realistic and feasible?? and ?What are the impacts of 100% RE on climate change?? The paper examines the global RE landscape, progress, and current status, focusing on increasing the RE share in the energy mix. It analyzes the feasibility of achieving 100% RE and its role in mitigating climate change at the global level. In this regard, the research, plans, and significant progress toward near 100% RE achievements in various regions and sectors are reviewed. The paper highlights innovative solutions, global policy landscapes, real-life examples, best practices, technical solutions, optimization methods, integration improvements, feasibility studies, market dynamics, and RE technology advancements and their role in this transition. A detailed analysis of the challenges facing this transition?including economic, environmental, technical, social, policy, standards, and energy efficiency aspects?is also discussed. Additionally, it provides insightful discussions on solutions and strategies to overcome these challenges, presenting a comprehensive perspective on the transition. Finally, the paper concludes with recommendations for future research directions. The insights provided contribute to the ongoing dialogue surrounding RE transitions, offering perspectives and considerations for policymakers, researchers, and stakeholders as they navigate the path toward a cleaner and more sustainable energy future for the planet. ? 2024 Elsevier Ltd